Comparison of mortality and short-term outcomes between classic, intubation-surfactant-extubation, and less invasive surfactant administration methods of surfactant replacement therapy - Kim, Seung Yeon; Lim, Jiseun; Shim, Gyu-Hong (Frontiers in Pediatrics, 2023)
Background: Intubation-Surfactant-Extubation (InSurE) and less invasive surfactant administration (LISA) are alternative surfactant replacement therapy methods for reducing the complications associated with invasive mechanical ventilation. This study aimed to compare the Classic, InSurE, and LISA methods in Very-Low-Birth-Weight infants (VLBWIs) in South Korea. Methods: The Korean Neonatal Network (KNN) enrolled VLBWIs born between January 1, 2019 and December 31, 2020. They were analyzed retrospectively to compare the duration of respiratory support, length of hospitalization, mortality, and short-term outcomes of the three groups. Results: The duration of invasive ventilator support was shorter in the following order: InSurE (3.99 ± 11.93 days), LISA (8.78 ± 29.32 days), and the Classic group (22.36 ± 29.94 days) (p = 0.014, p < 0.01) and InSurE had the shortest hospitalization (64.91 ± 24.07 days, p < 0.05) although the results couldn't adjust for confounding factor because of irregular distribution. InSurE had the lower risk of intraventricular hemorrhage (IVH) grade II-IV [odds ratio (OR) 0.524 (95% confidence interval (CI): 0.287-0.956), p = 0.035] than in the Classic group. Mortality was lower in the InSurE [OR 0.377 (95% CI: 0.146-0.978), p = 0.045] and LISA [OR 0.296 (95% CI: 0.102-0.862), p = 0.026] groups than in the Classic group. There was a reduced risk of moderate to severe bronchopulmonary dysplasia (BPD) [OR 0.691 (95% CI: 0.479-0.998, p = 0.049), OR 0.544 (95% CI: 0.355-0.831, p = 0.005), respectively], pulmonary hypertension [OR 0.350 (95% CI: 0.150-0.817, p = 0.015), OR 0.276 (95% CI: 0.107-0.713, p = 0.008), respectively], periventricular leukomalacia (PVL) [OR 0.382 (95% CI: 0.187-0.780, p = 0.008), OR 0.246 (95% CI: 0.096-0.627, p = 0.003), respectively], and patent ductus arteriosus (PDA) with treatment [OR 0.628 (95% CI: 0.454-0.868, p = 0.005), OR 0.467 (95% CI: 0.313-0.696, p < 0.001) respectively] in the InSurE and LISA groups compared to the Classic group. Conclusion: InSurE showed the lowest duration of invasive ventilator support, length of hospitalization. InSurE and LISA exhibited reduced mortality and decreased risks of moderate to severe BPD, pulmonary hypertension, PVL, and PDA with treatment compared to the Classic group.